Optimalisasi Publikasi Sekolah Berbasis Media Sosial melalui Analisis Kendala dan Pendampingan Guru di TK Widhya Brata: Pengabdian - Pancane, I Wayan Dikse; Suryadinatha, AAN. Oka; Adrama, Nyoman Gede; Anjani, Ketut; Arnaya, I Putu Budi; Ariawan, I Putu (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Abstract This community service analyzes the challenges of social media utilization and its impact on school publications at TK Widhya Brata. This report identifies various obstacles, such as limited human resources who lack specialized skills in social media management, a slow bureaucratic process for content approval, and facility limitations like unstable internet connections. The analysis uses Organizational Communication Theory to dissect internal and external barriers, and Lasswell's Communication Theory to evaluate the effectiveness of the publications. Findings indicate that these challenges lead to inconsistent, unappealing, and ineffective content publication on social media, failing to reach the target audience optimally. Consequently, this affects the school's image and its appeal to prospective parents and the wider community, which is analyzed using Brand Loyalty Theory. The study concludes that although TK Widhya Brata has significant potential, existing communication constraints hinder effective digital publication efforts. This report provides practical recommendations to address these issues, such as specific staff training and workflow simplification.